Analysis of Students' Difficulties in Developing English Listening Skills: A Case Study of SMA 3 Yogyakarta - Haris Dibdyaningsih; Mesrawati Rifai; S. SUMIHATUL UMMAH MS (Journal of Pedagogi, 2024)
This study aims to analyze the difficulties faced by 11th grade students of SMA Negeri 3 Yogyakarta in developing English listening skills. Listening skills are an important aspect of English language learning, especially in the context of globalization. However, students often face various challenges, such as limited vocabulary, grammatical understanding, poor audio quality, and environmental distractions, which hinder their abilities. This research used a case study approach with qualitative methods, involving 30 students selected by purposive sampling. Data were collected through questionnaires and semi-structured interviews, then analyzed using descriptive statistics and thematic analysis. The results showed that 70% of students had difficulties in vocabulary, 60% in grammar, 50% were affected by audio quality, and 65% faced anxiety while listening. Most students preferred interactive digital media, such as video and audio, which helped reduce anxiety and improve their comprehension. Technology integration in learning was identified as a potential solution to overcome such difficulties and increase students' learning motivation.